Pola Pemberian Makanan Pendamping ASI pada Anak Usia Bawah Dua Tahun Gizi Kurang di wilayah kerja Puskesmas Saiti: Pattern of Complementary Feeding for Breastfeeding to Children Under Two Years of Malnutrition in the work area of the Saiti Health Center - Rizka Abdussama; Ramli ramli; Yustiyanti Monoarfa; Muhammad Syahrir (Buletin Kesehatan MAHASISWA, 2023)
Masalah gizi kurang dan gizi buruk pada anak balita masih menjadi masalah gizi utama yang perlu mendapat perhatian.Secara langsung masalah gizi disebabkan oleh asupan yang kurang dan tingginya penyakit infeksi. Gizi merupakan kebutuhan yang sangat penting dalam proses pertumbuhan dan perkembangan bayi dan anak. Pemberian makan yang baik sejak lahir hingga usia dua tahun adalah salah satu upaya mendasar untuk menjamin pencapaian kualitas tumbuh kembang sekaligus memenuhi hak. Berdasarkan profil Dinas Kesehatan Kabupaten Banggai Tahun 2020 penderita gizi kurang sebanyak 8,3%. Berdasarkan data di Puskesmas Saiti terjadi peningkatan kasus gizi kurang pada tahun 2020 ke 2021 yaitu dari 11,18% menjadi 17,20%. Jenis Penelitian yang dilakukan adalah survey deskriptif yang bertujuan untuk melihat Pola Pemberian Makanan Pendamping ASI pada Anak Usia Bawah Dua Tahun Gizi Kurang di Wilayah Kerja Puskesmas Saiti. Pop ulasi dalam penelitian ini adalah seluruh bayi usia dua tahun gizi kurang pada tahun 2022 yang berjumlah 32. Penyajian data dilakukan setalah data diolah dan dianalisis kemudian disajikan dalam bentuk distribusi frekuensi disertai narasi untuk menarik kesimpulan. Hasil Penelitian Pola Pemberian Makanan Pendamping ASI pada Anak Usia Bawah Dua Tahun Gizi Kurang di Wilayah Kerja Puskesmas Saiti yaitu, sebanyak 24 (75%) baduta diberikan MP – ASI Lokal, sedangkan 8 (25%) baduta diberikan MP – ASI Pabrikan. Sebanyak 32 (100%) baduta diberikan Makanan Lumat Pada Usia 6 – 8 Bulan. Sebanyak 32 (100%) baduta diberikan Makanan Lunak pada Usia 9 – 12 Bulan. Sebanyak 32 (100%) baduta diberikan Makanan Padat pada Usia 13 – 24 Bulan. Sebanyak 30 (93,8%) baduta diberikan MP – ASI pada usia 6 – 8 Bulan sebanyak 2 – 3 kali sehari. Sedangkan, 9 – 12 bulan sebanyak 3 – 4 kali sehari 28 (87,5%) baduta. Dan 13 – 24 Bulan 3 – 4 kali sehari terdapat 27 (84,4%) baduta. Sebanyak 32 (100%) baduta diberikan MP – ASI dengan Hygiene yang baik dan, tepat waktu. Sebanyak 16 (50%) baduta diberikan MP ASI Lokal. Dan sebanyak 9 (28,1) baduta diberikan MP – ASI Lokal yaitu Bubur dicampur dengan dan daging. Dan sebanyak 7 (21,9%) baduta diberikan MP – ASI Pabrikan. Saran perlunya dilakukan upaya pemberday aan masyarakat dalam penyiapan MP – ASI Lokal yang bervariasi dan memenuhi kebutuhan gizi baduta. The problem of undernutrition and malnutrition in children under five is still a major nutritional problem that needs attention. Nutritional problems are directly caused by inadequate intake and high levels of infectious diseases. Nutrition is a very important need in the process of growth and development of infants and children. Proper feeding from birth to the age of two is one of the fundamental efforts to ensure quality growth and development while simultaneously fulfilling rights. Based on the Banggai District Health Office profile in 2020, 8.3% of people with malnutrition were malnourished. Based on data at the Saiti Health Center, there has been an increase in cases of malnutrition in 2020 to 2021, from 11.18% to 17.20%. This type of research is a descriptive survey that aims to see the pattern of complementary feeding to children under two years of age with malnutrition in the working area of the Saiti Health Center. The population in this study were all 32-year-old undernourished infants in 2022. The data was presented after the data was processed and analyzed and then presented in the form of a frequency distribution accompanied by a narration to draw conclusions. The results of the study on the pattern of providing complementary feeding to children under two years of age with malnutrition in the working area of the Saiti Health Center were 24 (75%) under-fives were given MP-ASI Local, while 8 (25%) were given MP-ASI Manufacturers. A total of 32 (100%) baduta were given crushed food at the age of 6-8 months. A total of 32 (100%) Baduta were given Soft Food at the Age of 9 -12 Months. A total of 32 (100%) children were given solid food at the age of 13 -24 months. A total of 30 (93.8%) children under two were given MP - ASI at the age of 6 - 8 months as much as 2-3 times a day. Meanwhile, 9-12 months as many as 3-4 times a day 28 (87.5%) baduta. And 13 – 24 Months 3-4 times a day there are 27 (84.4%) baduta. A total of 32 (100%) children under two were given MP - ASI with good hygiene and on time. A total of 16 (50%) chil dren under two were given MP ASI Local. And as many as 9 (28.1) children under two were given MP - Local ASI, namely porridge mixed with meat and porridge. And as many as 7 (21.9%) children under two were given MP - ASI Manufacturer. Suggestions for the need for community empowerment efforts in the preparation of local MP - ASI that are varied and meet the nutritional needs of under-fives.